Measuring and Evaluating Productivity Indicators of Selected Banks in Iran(With an Emphasis on Efficiency and Effectiveness) - Seyed Mohammadreza Seyed Nourani; abass shakeri; amir khadem alizadeh; reza vafaee yeganeh (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2018)
Productivity is a behavioral trait that relies on relationship optimization and interaction between internal and external factors. Productivity derives its vitality from the fact that when it increases, total output can increase without increasing the factors involved in production. This study aimed to evaluate productivity (efficiency and effectiveness) of select banks in Islamic Republic of Iran’s Interest-Free Banking system. By using a numeric index method, indices of labor productivity, Intermediary inputs productivity, capital productivity and total factor productivity were measured in select commercial banks with and without considering effectiveness factor. Our findings suggest that average growth of labor productivity, capital and intermediate consumption in selected banks in the period under review was descending, the average productivity growth of deposits in banks in the study period was 0.2% and average total factor productivity growth without and with equivalent effectiveness indicators were 1.82 and -4.2% respectively.